Navigating the Maze: Finding Placement for Industrial Attachment - Kiplagat , Hoseah; Wanjiku , Jennifer Khamasi; Karei , Rachel (African Journal of Education,Science and Technology (AJEST), 2013)
This paper is based on a study that was carried out among university students with the aim of finding out how they got placement for industrial attachment (IA) which is commonly referred to as Field Attachment (FA). Students are normally prepared adequately through interactive sessions with the members of staff of a given department. It is assumed that these sessions equip the students with the basic knowledge needed while they are on attachment. Over the years, it has emerged that many students take longer to find placement than others. A number of students take more than a month before they get placed. In 2012, we carried out a questionnaire survey after trainees returned to the university from a two month industrial attachment. The questionnaire is organized into 15 thematic areas most of which had sub-categories. Two (2) themes sought demographic information and details about the firms where students were placed, 4 thematic items were open ended and 9 were Likert Scale type ranging from strongly agree (SA) to strongly disagree (SD) or very likely (VL) to very unlikely (VU) or very satisfied (VS) to very dissatisfied (VD). A total of 35 questionnaires were administered using convenience sampling method to the students who were available during data collection period. The findings of the study revealed that majority of the students (48%) found places by applying directly to firms of their choice. A number secured placement through friends (26%), 11% were non-committal on how they found attachment firms, 9% were assisted by their guardians or parents, 3% got attached to firms where they previously worked, and another 3% did not respond to the item. None of the respondents acknowledged any assistance from the teaching department (0%). Consequently, it is recommended that training institutions should find placements for their students before IA start date to save time spent by students visiting industries in search of places.